2021
DOI: 10.1021/acs.jmedchem.1c00574
|View full text |Cite
|
Sign up to set email alerts
|

A Phenotypic Screen Identifies a Compound Series That Induces Differentiation of Acute Myeloid Leukemia Cells In Vitro and Shows Antitumor Effects In Vivo

Abstract: Induction of differentiation is a promising therapeutic strategy against acute myeloid leukemia. However, current differentiation therapies are effective only to specific patient populations. To identify novel differentiation agents with wider efficacy, we developed a phenotypic high-throughput screen with a range of genetically diverse cell lines. From the resulting hits, one chemical scaffold was optimized in terms of activity and physicochemical properties to yield OXS007417, a proof-of-concept tool compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Starting from confirmed hits, further optimization afforded the lead compounds OXS007417 2 and OXS007464 3 , both of which had higher potency and improved ADME properties relative to the starting compound ( Figures 3 A and 3B, detailed chemistry in ( Josa-Cullere et al., 2021 )). We confirmed that both OXS007417 2 and OXS007464 3 also caused differentiation of AML cell lines by showing that they upregulated CD11b cell surface expression in HL-60 cells with comparable EC 50 values of 57 ± 3 nM and 36 ± 1 nM respectively ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…Starting from confirmed hits, further optimization afforded the lead compounds OXS007417 2 and OXS007464 3 , both of which had higher potency and improved ADME properties relative to the starting compound ( Figures 3 A and 3B, detailed chemistry in ( Josa-Cullere et al., 2021 )). We confirmed that both OXS007417 2 and OXS007464 3 also caused differentiation of AML cell lines by showing that they upregulated CD11b cell surface expression in HL-60 cells with comparable EC 50 values of 57 ± 3 nM and 36 ± 1 nM respectively ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…At present, the treatment of leukemia is mainly based on the combination of chemotherapy and targeted therapy, but there are obvious side effects and a high recurrence rate. The differentiation induction therapy represented by all-trans retinoic acid is one of the best methods for the treatment of leukemia (9)(10)(11); in that, the leukemia cells are induced to differentiate into mature promyelocytes by all trans retinoic acid (ATRA) and their malignant proliferation is inhibited. It is precisely because of this selective effect on leukemia cells that it does not affect normal hematopoietic and immune functions, making it a research hotspot (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional chemotherapy, induced differentiation therapy has become an ideal method for the treatment of leukemia due to its non-toxic side effects (7,8). However, so far, only patients with acute promyelocytic leukemia could get the complete remission induced by differentiation-inducing drugs such as all-trans retinoic acid; other types of leukemia have not benefited from them (9)(10)(11). Therefore, it is necessary to actively explore new intervention targets and corresponding targeted drugs on the basis of in-depth exploration of the key mechanisms of leukemia differentiation disorders.…”
Section: Mir-let-7c-3p Targeting On Egr-1 Contributes To the Committe...mentioning
confidence: 99%
“…Whilst these represent significant steps forward in terms of therapeutic options for patients, the limitation of these agents is that they target specific genetic lesions and are effective only in specific patient subtypes. Thus, we and others [15,16] have been interested in identifying compounds using alternative mechanisms and which are able to induce differentiation of AML cells, regardless of their subtype or mutation status. The hope is that such compounds will be effective in wider patient populations and will avoid some of the limitations of therapies designed for specific targets [17].…”
Section: Introductionmentioning
confidence: 99%
“…Within our effort to identify novel differentiating agents for AML, we developed a phenotypic screen with different AML cell lines representing different disease subtypes and measured the myeloid marker CD11b as a primary readout. We identified several compound classes, some of which showed in vivo efficacy [15,18]. Herein, we report the identification and structure-activity relationship (SAR) studies of one of these compound classes, which possesses a 1,5-dihydrobenzo[e][1,4]oxazepin-2(3H)-one core structure.…”
Section: Introductionmentioning
confidence: 99%